Cover Picture: Densely Packed Hydrophobic Clustering: Encapsulated Valerates Form a High‐Temperature‐Stable Mo132 Capsule System (Angew. Chem. Int. Ed. 23/2016). Issue 23 (6th May 2016) - Garai, Somenath; Bögge, Hartmut; Merca, Alice; Petina, Olga A.; Grego, Alina; Gouzerh, Pierre; Haupt, Erhard T. K.; Weinstock, Ira A.; Müller, Achim
Abstract : Porous spherical nanocontainers … … densely packed with valerates (pictured as juggling balls) are very stable and indicate the unique possibility of hydrophobic clustering inside a cavity, as reported by A. Müller and co‐workers in their Communication onpage 6634 ff. The clusters remain intact at temperatures of up to nearly the boiling point of water (© jokatoons/bildkistl, Fotolia.com).